Zinc prevents mitochondrial superoxide generation by inducing mitophagy in the setting of hypoxia/reoxygenation in cardiac cells. (2nd January 2018) - Bian, Xiyun; Teng, Tianming; Zhao, Huanhuan; Qin, Jiangyu; Qiao, Zhen; Sun, Yuemin; Liun, Zhiqiang; Xu, Zhelong
Abstract: Zinc plays a role in autophagy and protects cardiac cells from ischemia/reperfusion injury. This study aimed to test if zinc can induce mitophagy leading to attenuation of mitochondrial superoxide generation in the setting of hypoxia/reoxygenation (H/R) in cardiac cells. H9c2 cells were subjected to 4 h hypoxia followed by 2 h reoxygenation. Under normoxic conditions, treatments of cells with ZnCl2 increased both the LC3-II/LC3-I ratio and GFP-LC3 puncta, implying that zinc induces autophagy. Further experiments showed that endogenous zinc is required for the autophagy induced by starvation and rapamycin. Zinc down-regulated TOM20, TIM23, and COX4 both in normoxic cells and the cells subjected to H/R, indicating that zinc can trigger mitophagy. Zinc increased ERK activity and Beclin1 expression, and zinc-induced mitophagy was inhibited by PD98059 and Beclin1 siRNA during reoxygenation. Zinc-induced Beclin1 expression was reversed by PD98059, implying that zinc promotes Beclin1 expression via ERK. In addition, zinc failed to induce mitophagy in cells transfected with PINK1 siRNA and stabilized PINK1 in mitochondria. Moreover, zinc-induced PINK1 stabilization was inhibited by PD98059. Finally, zinc prevented mitochondrial superoxide generation and dissipation of mitochondrial membrane potential (Δ Ψ m ) at reoxygenation, which was blocked by both the Beclin1 and PINK1 siRNAs, suggesting that zinc prevents mitochondrial oxidative stress through mitophagy. In summary, zinc induces mitophagy through PINK1 and Beclin1 via ERK leading to the prevention of mitochondrial superoxide generation in the setting of H/R. Clearance of damaged mitochondria may account for the cardioprotective effect of zinc on H/R injury.